Small private online courses (SPOC) as a new approach to higher education - Nahornyi, V. V.; Nahorna, N. O.; Murzina, O. A.; Tyrsa, T. O.; Нагорний, Володимир Володимирович; Нагорна, Наталія Олександрівна; Мурзіна, Олена Анатоліївна (My University, 2021)
Small Private Online Course (SPOC) are a new type of online class that allow anyone, anywhere, to participate via video lectures, computer graded tests, and discussion forums. This article will give a basic overview of what SPOCs and how they work.
Keywords: Small Private Online Course (SPOC); Massive Open Online Courses (MOOCs); EdX; higher education; blended learning